Controls on channel deposits of highly variable rivers: Comparing hydrology and event deposits in the Burdekin River, Australia. Issue 5 (28th March 2020) - Alexander, Jan; Herbert, Christopher M.; Fielding, Christopher R.; Amos, Kathryn J.
Abstract: Discharge event frequency, magnitude and duration all control river channel morphology and sedimentary architecture. Uncertainty persists as to whether alluvial deposits in the rock record are a time‐averaged amalgam from all discharge events, or a biased record of larger events. This paper investigates the controls on channel deposit character and subsurface stratigraphic architecture in a river with seasonal discharge and very high inter‐annual variability, the Burdekin River of north‐east Australia. In such rivers, most sediment movement is restricted to a few days each year and at other times little sediment moves. However, the maximum discharge magnitude does not directly correlate with the amount of morphological change and some big events do not produce large deposits. The Burdekin channel deposits consist of five main depositional elements: (i) unit bars; (ii) vegetation‐generated bars; (iii) gravel sheets and lags; (iv) antidune trains; and (v) sand sheets. The proportions of each depositional element preserved in the deposits depend on the history of successive large discharge events, their duration and the rate at which they wane. Events with similar peak magnitude but different rate of decline preserve different event deposits. The high intra‐annual and inter‐annual discharge variability and rapid rate of stage change make it likely that small to moderate‐scale bed morphology will be in disequilibrium with flow conditions most of the time. Consequently, dune and unit bar size and cross‐bed set thickness are not good indicators of event or channel size. Antidunes may be more useful as indicators of flow conditions at the time they formed. Rivers with very high coefficient of variance of maximum discharge, such as the Burdekin, form distinctive channel sediment bodies. However, the component parts are such that, if they are examined in isolation, they could lead to misleading interpretation of the nature of the depositional environment if conventional interpretations are used.